眼科装置 (2024)
本发明提供一种眼科装置。眼科装置具有拍摄受检眼的晶状体的层析图像的拍摄部和运算部。运算部被构成为能够执行边界检测处理、异常检测处理和解析处理，其中，所述边界检测处理是检测由拍摄部拍摄到的受检眼的晶状体的层析图像中的组织间的边界的处理；所述异常检测处理是检测各组织的异常的处理，所述各组织由通过边界检测处理检测到的边界来界定。所述解析处理是指对与通过异常检测处理检测到的异常建立了对应关系的解析项目进行解析的处理。据此，能够高精度地解析受检眼的晶状体。 An ophthalmic device may include: an image capturing unit configured to capture a tomographic image of a crystalline lens of a subject eye; a processor; and a memory storing computer-readable instructions therein. The computer-readable instructions, when executed by the processor, may cause the processor to execute: detecting a boundary between tissues in a tomographic image of the crystalline lens of the subject eye captured by the image capturing unit; determining whether the tissues defined by the boundary include an abnormality; and analyzing an analysis item associated with the abnormality.